Discussion and argumentation about the impact of cultural experience on emotional intelligence measurement questionnaires - Lippels, Thomas Werner (2009)
The objective of this dissertation is to evidence the correlation between cultural experience and Emotional Intelligence (EI) which can influence the outcome of Emotional Intelligence Questionnaires (EIQ). To do so, three defined variables, such as age, language abilities and foreign experience have been taken into consideration to present Cultural Intelligence [CI] and students from different nationalities have taken one elected EIQ in two different languages. The correlation between the two test results, based on the participants age, language abilities and foreign experience have been observed, and discussed. The results of the study indicate that all three variables have an impact on EI, whereas age and foreign experience seemed to be more important than language abilities. As it is proposed that EI contributes to effective leadership, it is required to study if this theory is culturally influenced. This discussion is needed as the construct of EI became widely used in Psychology and Human Resource Management (HRM) to evaluate individual and team performance, while most accessible questionnaires have been constructed by North American researchers and are usually available in English. Therefore the use of well established EI questionnaires, evaluating trait or ability EI needs to be investigated to avoid conclusions neglecting possible cross-cultural differences and influencing evaluation standards. It is necessary to mention, that because of the limitation of the work, the cultural dependency of EI questionnaires will be studied while focusing on verbal understanding and by using one specific Questionnaire as example, namely the Wang and Law Emotional Intelligence Scale [WLEIS].